Tantangan Pancasila di Era Globalisasi - Desilva, Keysialova Niswan Arva; Ar Raihan, Ibnu Sabiq; Farros, Muhammad Nizar Aufa; Suparmi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Globalization has a broad impact on all aspects of life in Indonesia, including the values ​​of Pancasila as the ideology and foundation of the state. The development of technology, communication, and cultural currents can pose serious challenges to the existence of the nation’s core values ​​that serve as the way of life of the Indonesian people. This study aims to analyze the influence of globalization and the resilience of Pancasila values, explain the implementation of Pancasila as the foundation of the state and the basis of defense, and formulate strategies for strengthening Pancasila values ​​amidst the currents of globalization. The research method used is descriptive qualitative with a literature review approach. Data were collected from various relevant national scientific journals and analyzed qualitatively. The results of the study indicate that globalization has an impact on the movement of Pancasila values, especially in moral, social, and cultural aspects. However, Pancasila remains strategic as the nation’s ideology. In conclusion, the strengthening and actualization of Pancasila values ​​must be carried out continuously through education and policies, as well as the use of technology. Pancasila must always be maintained as a dynamic ideology that serves as the way of life of the Indonesian nation.